2015
DOI: 10.1007/s10439-015-1465-6
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Remodeling of Cardiac Tissue: A Comprehensive Approach Based on Confocal Microscopy and 3D Reconstructions

Abstract: Microstructural characterization of cardiac tissue and its remodeling in disease is a crucial step in many basic research projects. We present a comprehensive approach for three-dimensional characterization of cardiac tissue at the submicrometer scale. We developed a compression-free mounting method as well as labeling and imaging protocols that facilitate acquisition of three-dimensional image stacks with scanning confocal microscopy. We evaluated the approach with normal and infarcted ventricular tissue. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 44 publications
2
56
1
Order By: Relevance
“…T-system remodeling in failing rodent hearts has been studied extensively, but t-system components as found in human heart failure or in a porcine infarct model (Pinali et al, 2017) have not been identified. In contrast, images of remodeled t-tubules published by others (Driesen et al, 2007) and us (Seidel et al, 2016), including the present study, indicate that t-system remodeling in rabbit resembles the human phenotype. Driesen et al described vacuole-like structures in cardiomyocytes adjacent to the infarct border in rabbit and suggested that “the vacuoles represent plasma membrane invaginations and/or dilatations of t-tubular structures.” Based on our three-dimensional reconstructions (Fig.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…T-system remodeling in failing rodent hearts has been studied extensively, but t-system components as found in human heart failure or in a porcine infarct model (Pinali et al, 2017) have not been identified. In contrast, images of remodeled t-tubules published by others (Driesen et al, 2007) and us (Seidel et al, 2016), including the present study, indicate that t-system remodeling in rabbit resembles the human phenotype. Driesen et al described vacuole-like structures in cardiomyocytes adjacent to the infarct border in rabbit and suggested that “the vacuoles represent plasma membrane invaginations and/or dilatations of t-tubular structures.” Based on our three-dimensional reconstructions (Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…We used 12 male New Zealand White rabbits of 2.5 to 3kg. In 6 randomly selected animals, left-ventricular MI was created by ligation of the left circumflex artery as previously described (Hu et al, 2010; Seidel et al, 2016). Successful ligation was confirmed by ST elevation in ECG recordings and epicardial demarcation of the infarcted area.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations